The Investigation and Elimination of Public Procurement Fraud in Government Sectors (A Case Study in Indonesia's Procurement System: Cases from 2006 to 2012) - Maulidi, Ach (International Journal of Economics and Financial Issues, 2017)
This paper offers insights to enhance our understanding of public procurement fraud through analyzing current 173 cases during 2006 to 2012 in Indonesia's procurement system using various points of view. These insights are synthesized from current research findings and contemporary thinking elaborated by practical knowledge and skills, the aim of which is to produce accurate analysis. The main aim of this paper is to participate in terms of combating procurement fraud by suggesting plausible and applicable measures in relation to investigating and preventing this kind of financial crime, and in terms of developing theory. The result of this study confirms that detection and deterrence of public procurement fraud are still longstanding antirust problems, made difficult because collusive arrangements among bidders, between contractors and employers, and sole procurement committees are usually surreptitious. Because of complex and confusing procurement mechanisms with blurred and overlapping jurisdictions, information asymmetry and conflict of interest, the corrupt behaviors is likely to continue to flourish. This study reveals that cooperation between government and private sector to maintain high standards of integrity is viewed the most effective aspect that should be taken into account prudently when designing precaution measures for procurement fraud. Keywords: Fraud, Public Procurement, Investigating, Preventing JEL Classifications: M41, M4